A carbon and nitrogen isotope perspective on ancient human diet in the British Isles. (January 2022) - Bird, Michael I.; Haig, Jordahna; Ulm, Sean; Wurster, Christopher
Abstract: The stable carbon ( δ 13 C) and nitrogen ( δ 15 N) isotope composition of human bone collagen is increasingly used to investigate past mobility and subsistence strategies. This study presents a compilation of 1298 carbon and nitrogen isotope analyses of archaeological human bone collagen from the British Isles spanning much of the Holocene, along with a compilation of 4148 analyses of modern and ancient isotope analyses from the major marine and terrestrial dietary resources from the same region. We convert ancient human stable isotope data to modern diet equivalent (MDE) values for humans, and convert the isotope composition of ancient dietary items to modern tissue equivalent (MTE) isotope values. These conversions enable a direct comparison of ancient and modern datasets. Results for food groups (plants, grain, herbivores, omnivores, shellfish, freshwater fish and marine fish) show a remarkably broad range of δ 13 CMTE values from ∼-36 to −7‰ and δ 15 NMTE values from ∼-2 to +21‰ and we provide estimates for each food type that can be used in dietary reconstruction in the absence of site-specific data. We further show that there is no significant change in terrestrial stable isotope baseline values over the Holocene, with observed variability in baseline values due to local eco-physiological, edaphic and microclimatic factors. The range of values expressed in the human sample set from the beginning of the Iron Age is relatively tightly clustered with 50% of all human modern diet equivalent results falling within a ∼2‰ range in δ 13 CMDE values (−25.5 to −27.5‰) and a ∼3.5‰ range in δ 15 NMDE values from (+4‰ to +8‰). From the Iron Age to post-medieval times there is a consistent progressive shift to higher δ 13 CMDE and δ 15 NMDE values at the population level. This shift likely reflects a combination of successive innovations associated with food production, preservation and transport that enabled a broader cross-section of the population of the British Isles to incorporate a higher proportion of animal, and particularly marine protein, into their diets. Highlights: Compilation of the C and N isotope composition 1298 human and 4148 dietary samples from Britain. Compilation covers the period from the Mesolithic to the 19th Century. Dietary baseline has not varied over the period, but there is significant spatial heterogeneity. Significant temporal changes in human diet are manifest across the entire British Isles. The compilation provides the basis for developing a C and N isoscape for Britain.